2006
DOI: 10.1021/np050449b
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Bisanthraquinones Produced by a Streptomycete Isolated from a Cyanobacterium Associated with Ecteinascidia turbinata

Abstract: Chemical studies of a streptomycete isolated from a cyanobacterium associated with the tropical tunicate Ecteinascidia turbinata led to the bioassay-guided purification of two antibacterial bisanthraquinone metabolites and a cytotoxic artifact. The structures, including relative configurations of these octacyclic compounds, were established by spectroscopic analyses. Their potent antibacterial properties (IC(50) = 0.15-130 microM) versus methicillin-resistant Staphylococcus aureus and vancomycin-resistant Ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 11 publications
(21 reference statements)
4
39
0
Order By: Relevance
“…In accord with the values reported by Rowley and coworkers1,2, (+)- 1 (natural enantiomer) exhibited strong bactericidal activity against Gram-positive pathogens (MRSA and VRE). Given the architectural complexity of 1 it is notable that the unnatural enantiomer [(–)- 1 ] displayed almost similar activity.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In accord with the values reported by Rowley and coworkers1,2, (+)- 1 (natural enantiomer) exhibited strong bactericidal activity against Gram-positive pathogens (MRSA and VRE). Given the architectural complexity of 1 it is notable that the unnatural enantiomer [(–)- 1 ] displayed almost similar activity.…”
Section: Resultssupporting
confidence: 89%
“…Synthetic (+)- 1 exhibited identical physical properties to those reported for the natural product and essentially the same optical rotation ([α]normalD20 ( c = 0.14 in CHCl 3 ) = +411.4) as that of natural (+)- 1 ([α]normalD20 ( c = 0.14 in CHCl 3 ) = +403.1, and so did (–)- 1 , except for its optical rotation, which was of the opposite sign ([α]normalD20 ( c = 0.14 in CHCl 3 ) = –417.1) 26. Because our data for synthetic (+)- 1 matched both the data reported by Rowley1 and in the Japanese patent,3 we concluded that all three compounds are identical, that is to say one and the same.…”
Section: Resultssupporting
confidence: 77%
“…The bisanthraquinone antibiotic BE-43472B ( 1 , Figure 1), which was isolated by Rowley and coworkers from a strain of streptomycete found in green algae,1 has been shown to have significant bactericidal activity against a variety of pathogens, including some of those that demonstrate resistance to commonly used antibiotics 2. In addition to antibiotic activity, this compound previously appeared in a Japanese patent, where it was claimed to be an antitumor agent 3.…”
Section: Introductionmentioning
confidence: 99%
“…A decade later, the compounds were also reported as natural products from a marine Streptomyces strain (N1-78-1) isolated from cultured cells of an unidentified cyanobacterium (URI strain N36-11-10), itself collected from a Puerto Rican ascidian, Ecteinascidia turbinata [53,54]. In this latter study, the relative stereochemistry of the compounds was defined and the compounds were determined to have potent antibacterial activity against MRSA and VRE, as well as cytotoxic activity against HCT-116 cells.…”
Section: Anti-methicillin-resistant Staphylococcus Aureus (Mrsa) Amentioning
confidence: 99%